Fe3O4-PDA-lipase as surface functionalized nano biocatalyst for the production of biodiesel using waste cooking oil as feedstock: characterization and process optimization - Touqeer, Tooba; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Irfan, Ahmad; Akram, Sadia; Shabbir, Aroosh; Rashid, Umer; Nehdi, Imededdine Arbi; Choong, Thomas Shean Yaw (MDPI, 2020)
Synthesis of surface modified/multi-functional nanoparticles has become a vital research area of material science. In the present work, iron oxide (Fe3O4) nanoparticles prepared by solvo-thermal method were functionalized by polydopamine. The catechol groups of polydopamine at the surface of nanoparticles provided the sites for the attachment of Aspergillus terreus AH-F2 lipase through adsorption, Schiff base and Michael addition mechanisms. The strategy was revealed to be facile and efficacious, as lipase immobilized on magnetic nanoparticles grant the edge of ease in recovery with utilizing external magnet and reusability of lipase. Maximum activity of free lipase was estimated to be 18.32 U/mg/min while activity of Fe3O4-PDA-Lipase was 17.82 U/mg/min (showing 97.27% residual activity). The lipase immobilized on polydopamine coated iron oxide (Fe3O4_PDA_Lipase) revealed better adoptability towards higher levels of temperature/pH comparative to free lipase. The synthesized (Fe3O4_PDA_Lipase) catalyst was employed for the preparation of biodiesel from waste cooking oil by enzymatic transesterification. Five factors response surface methodology was adopted for optimizing reaction conditions. The highest yield of biodiesel (92%) was achieved at 10% Fe3O4_PDA_Lipase percentage concentration, 6:1 CH3OH to oil ratio, 37 °C temperature, 0.6% water content and 30 h of reaction time. The Fe3O4-PDA-Lipase activity was not very affected after first four cycles and retained 25.79% of its initial activity after seven cycles. The nanoparticles were characterized by FTIR (Fourier transfer infrared) Spectroscopy, XRD (X-ray diffraction) and TEM (transmission electron microscopy), grafting of polydopamine on nanoparticles was confirmed by FTIR and formation of biodiesel was evaluated by FTIR and GC-MS (gas chromatography-mass spectrometry) analysis.